Innovations in Christian Education: A Multisensory Approach to Spiritual Learning - Rezeki Putra Gulo; Nikarni Zai (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This research explores innovations in Christian education through the application of a multisensory approach to spiritual learning. By using a phenomenology-based qualitative research method through literature research, this study aims to understand how a multisensory approach can improve the effectiveness of spiritual learning holistically. The main problem identified is the challenge in conveying abstract theological concepts to students, especially in the digital era that demands relevant and interesting learning methods. The novelty of the research lies in the integration of multisensory approaches with modern technologies, such as augmented reality and interactive applications, to create immersive sense-based learning experiences. The results of the study show that the multisensory approach enriches the learning process by increasing information retention, emotional engagement, and internalization of spiritual values. The findings also confirm that multisensory experiences are able to bridge the abstraction of Christian teachings with concrete experiences, creating a deeper connection between learners and faith values. The contributions of this research include the development of relevant, adaptive, and transformative Christian education strategies, as well as the provision of a theoretical foundation for the implementation of a multisensory approach in various educational contexts. This research provides new insights for Christian educators in presenting spiritual learning that is more holistic and contextual.